Nilai Sosial pada Kumpulan Cerpen Sebelum Telepon Berdering Karya Kun Andyan Anindito dengan Pendekatan Sosiologi Sastra - Riyanto Mahaputro; Siti Fatimah; Setia Naka Andrian (Universitas PGRI Semarang, 2023)
This study aims to describe how the social values contained in the collection of short stories â€œBefore the Telephone Ringsâ€ by Kun Andyan Anindito with a sociological approach to literature. The research method used in this research is qualitative. The research data comes from a collection of short stories before the telephone rings. The data collection technique used is listen and note. The data analysis technique uses content analysis. The results of the study found 37 data related to social values contained in 11 short stories including â€œHe Shouldn't Crave Ratsâ€ contains the value of love, the value of responsibility, and the value of harmony in life. â€œPoladodo camerasâ€ contain the value of compassion and responsibility. â€œForgiveness cakesâ€ contain the values of responsibility and harmony in life. â€œCan Mr. Judge Help Meâ€ contains the value of compassion, the value of responsibility, and the value of harmony in life. â€œThe word Rottenâ€ contains the value of love and responsibility. â€œBefore the Phone Ringsâ€ contains the value of compassion and the value of harmony in life. â€œBefore and After I Dieâ€ contains the value of love and the value of harmony in life. â€œThe intersectionâ€ contains the value of love and the value of harmony in life. â€œThe narrator, the Woman, and the Man Beside herâ€ contain the values of compassion and the value of responsibility. â€œThe Woman Who Waitsâ€ contains the value of love and the value of responsibility. â€œRetirement and Other Plansâ€ contain the value of compassion.ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan bagaimana nilai sosial yang terdapat dalam kumpulan cerpen Sebelum Telepon Berdering karya Kun Andyan Anindito dengan pendekatan sosiologi sastra. Metode penelitian yang digunakan pada penelitian ini ialah kualitatif. Data penelitian berasal dari buku kumpulan cerpen â€œSebelum Telepon Berderingâ€. Teknik pengumpulan data yang digunakan ialah simak dan catat. Teknik analisis data menggunakan content analysis. Hasil penelitian ditemukan 37 data terkait nilai sosial yang terdapat pada 11 cerpen di antaranya â€œMestinya Dia Tak Mengidam Tikusâ€ memuat nilai kasih sayang, nilai tanggung jawab, dan nilai keserasian hidup. Cerpen â€œKamera Poladodoâ€ memuat nilai kasih sayang dan tanggung jawab. â€œKue-kue Ampunanâ€ memuat nilai tanggung jawab dan keserasian hidup. Cerpen â€œApakah Tuan Hakim Bisa Membantu Sayaâ€ memuat nilai kasih sayang, nilai tanggung jawab, dan nilai keserasian hidup. Cerpen â€œKata Busukâ€ memuat nilai kasih sayang dan tanggung jawab. Cerpen â€œSebelum Telepon Berderingâ€ memuat nilai kasih sayang dan nilai keserasian hidup. CerpenÂ â€œSebelum dan Sesudah Aku Matiâ€ memuat nilai kasih sayang dan nilai keserasian hidup. â€œPersimpanganâ€ memuat nilai kasih sayang dan nilai keserasian hidup. Cerpen â€œNaratorâ€, Perempuan, dan Lelaki di Sampingnyaâ€ memuat nilai kasih sayang dan nilai tanggung jawab. â€œPerempuan yang Menungguâ€ memuat nilai kasih sayang dan nilai tanggung jawab. â€œPensiun dan Rencana yang Lainâ€ memuat nilai kasih sayang.